Upaya Meningkatkan Hasil Belajar Sejarah Melalui Model Pembelajaran Inside Outside Circle pada Siswa Kelas X Fm 3 Semester Genap SMK Negeri 7 Bandar Lampung - Betira, Willya; Suryati, Wawat; Febrianti, Aurora Nandia (Universitas Batanghari Jambi, 2023)
The problems in this study are related to the difficulty of students in working on tests, learning that is still conventional, the lack of active students in learning and the inability of students to draw conclusions from the material being studied. One of the learning models that can activate students is the inside outside circle (IOC) learning model. The purpose of this study was to determine the increase in history learning outcomes using the inside outside circle (IOC) learning model in class X FM 3 SMK Negeri 7 Bandar Lampung. This type of research is Classroom Action Research (CAR), which consists of 2 cycles where each cycle is held in four meetings. Research procedures include planning, implementation of action, observation and reflection. The subjects in this study were 38 students of class X FM 3 of SMK Negeri 7 Bandar Lampung. Data collection techniques used are observation, tests, and documentation. Data analysis techniques, namely quantitative and qualitative data. The results showed that in the first cycle, the percentage of completeness was 63.16% with an average score of 71.68. Then in cycle II there was a very significant increase where the percentage of completeness was 86.84% with an average score of 78.11. Based on the results of the research above, it can be concluded that the application of the inside outside circle (IOC) learning model can improve the history learning outcomes of class X FM 3 students of SMK Negeri 7 Bandar Lampung for the 2022/2023 academic year.